EVALUATING POLITICAL SPEECH TRANSLATION: A CAN-BASED COMPARATIVE ANALYSIS OF DONALD TRUMP’S INAUGURATION ADDRESS INTO INDONESIAN - Saiyidinal Firdaus (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2026)
Political speeches are high-stakes institutional texts in which ideology, agency, and evaluative stance are strategically organized, and their translation constitutes an integral part of political meaning-making rather than a neutral transfer. This study investigates how political meaning is recontextualized in Indonesian translations of Donald Trump’s 2017 Inauguration Address. The study aims to identify recurrent translation problems, examine how these problems pattern across linguistic and ideological layers, and explain their consequences for political accountability and stance reconstruction. Adopting a qualitative critical-comparative design, the research applies a CAN-based (Critical Analogy Network) framework that integrates Critical Discourse Analysis, appraisal theory, and lexico-grammatical analysis. Multiple Indonesian translations of the address were aligned and analyzed to trace shifts at textual–constructional, interpersonal–evaluative, and contextual–ideological levels. The findings reveal systematic and non-random translation problems, notably the de-agentivization of political action through passivization and nominalization, the moderation of interpersonal stance via modal weakening and appraisal recalibration, and the attenuation of populist antagonism through ideological reframing. These shifts operate as interconnected networks rather than isolated deviations, cumulatively transforming explicit political commitments into more neutralized and institutionally restrained narratives. The study demonstrates that political speech translation functions as ideologically consequential recontextualization shaped by constrained translator agency. By operationalizing translation problems as patterned networks, this research advances critical translation evaluation and offers a replicable framework for analyzing political discourse translation in mediatized contexts.